AI in Islamic finance: Global trends, ethical implications, and bibliometric insights - Iqbal, Muhammad Saeed; Sukamto, Fifi Anti Mapika Sari Binti; Norizan, Siti Noraisyah Binti; Mahmood, Shanayyara; Fatima, Arooj; Hashmi, Faiza (Review of Islamic Social Finance and Entrepreneurship, 2025)
Purpose – This study explores the integration of Artificial Intelligence (AI) in Islamic finance, analyzing global trends, ethical implications, and future research directions. The purpose is to assess AI’s role in enhancing Sharia compliance, regulatory adherence, and operational efficiency in Islamic financial institutions.Methodology – Using a bibliometric analysis approach, this research examines publications from 2010 to 2023 indexed in Scopus and Web of Science. Keywords such as Islamic finance, "artificial intelligence, AI in finance, Sharia compliance, and globalization guided the search. Analytical tools, including VOSviewer and CiteSpace, were employed to visualize publication trends, citation networks, and influential research contributions from key countries like Pakistan, Malaysia, Turkey, Saudi Arabia, Indonesia, Qatar, Iran, and the UAE.Findings – The research indicate that AI significantly enhances financial inclusion, risk assessment, compliance automation, and customer service in Islamic finance. Key research areas highlight AI-driven solutions for Sharia-compliant financial products, ethical considerations, and regulatory frameworks. However, limitations exist, as this study focuses only on English-language publications, potentially omitting critical insights from non-English sources.Implications – This research contributes to the understanding of AI's role in Islamic finance, offering practical implications for financial institutions seeking to integrate AI for efficiency, transparency, and compliance. Originality – It provides an original bibliometric perspective on AI applications in Islamic finance, underscoring the sector’s potential for innovation and sustainable growth in a globalized financial landscape.